Effects of inclination angle on natural convection in an inclined open porous cavity with non-isothermally heated wall - Öztop, Hakan Fehmi; Al-Salem, Khaled; Varol, Yasin; Pop, Ioan; Firat, Mujdat (Emerald Group Publishing Ltd, 2012)
Ptapose - The purpose of this numerical study is to investigate the effects of inclination angle and non-isothermal wall boundary conditions in a partially open cavity filled with a porous medium. Design/methodology/approach - In this study, the governing dimensionless equations were written using Brinkman-Forchheimer model. They are numerically solved by using finite volume method with SIMPLE solution algorithm by applying open boundary conditions in one side. The opposed side of the open cavity is under non-isothermal boundary conditions. Findings - Results are presented by streamlines, isotherms, velocity and temperature profiles as well as the local and mean Nusselt numbers for different values of the governing parameters such as Grashof numbers, porosity, amplitude of sinusoidal function and inclination angle of the cavity. It is found that inclination angle is the most important parameter on the temperature and flow field. Originality/value - The originality of this study is the open sided enclosure filled with porous media and non-isothermal wall.
Keywords: Natural convection; Open cavity; Inclination angle; Porous media; Porous materials; Flow; Convection